Photo-Oxidation of Therapeutic Protein Formulations: From Radical Formation to Analytical Techniques - Elena Hipper; Michaela Blech; Dariush Hinderberger; Patrick Garidel; Wolfgang Kaiser (MDPI AG, 2021)
UV and ambient light-induced modifications and related degradation of therapeutic proteins are observed during manufacturing and storage. Therefore, to ensure product quality, protein formulations need to be analyzed with respect to photo-degradation processes and eventually protected from light exposure. This task usually demands the application and combination of various analytical methods. This review addresses analytical aspects of investigating photo-oxidation products and related mediators such as reactive oxygen species generated via UV and ambient light with well-established and novel techniques.